A Wheeled Obstacle Avoidance Robot Based On Arduino Microcontroller by fuzzy controller - De Van Pham (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
In this paper, one of the basic functions that each self-propelled robot must have is to detect and avoid obstacles during movement, while still performing current tasks such as orbiting, tracking. The paper presents studies on the fuzzy controller combination to perform the functions of tracking and avoiding obstacles for a wheeled self-propelled robot, with two independently controlled active wheels. The ultrasonic sensors are used to detect and determine the distance from the robot to the obstacle, as input data for the obstacle avoidance fuzzy controller. The experiments with different types of obstacles and movement patterns in the laboratory environment gave good results, showing the correctness of the algorithm and the effective working ability of the combined fuzzy controller.